PROJECT-BASED LEARNING APPROACH TO IMPROVE STUDENTS’ WRITING SKILL - Dedeh Eha Zulaeha; Dian Priyantini Marpaung (PROJECT (Professional Journal of English Education), 2020)
This research was held during the internship at SMPK BPK PENABUR Cimahi by taking the material taught in English lesson for 8th grade students at first semester. The objective of this research is to find out the improvement of writing imperative sentence using Project-Based Learning approach. The use of Project Based Learning approach suited with the Kurikulum 2013, which has been used by this school since 2013. The method used Classroom Action Research (CAR), which held on two cycles for seven meetings. Each cycle covered the step of planning, acting, observing and reflecting. The data was collected from test and observation. The data from test showed that treatments are successful in improving writing imperative sentences skill for the students. The improvements covered two points, (1) improvement on their mean score. Mean score of pre-test was 54.967, mean score of post-test1was 64.467 and mean score of post-test2 was 80.033. (2) Improvement of their behaviors. Their activeness individually and participation in the group indicated that the Project Based Learning approach was the right approach to be applied in the classroom teaching. Keywords:  CAR, Project-Based Learning Approach, Writing Skill